2014
DOI: 10.1159/000369661
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-212 Inhibits Osteosarcoma Cells Proliferation and Invasion by Down-Regulation of Sox4

Abstract: Background: Multiple MicroRNAs (miRNAs) have been identified in the development and progression of osteosarcoma. However, the expression and roles of miR-212 in osteosarcoma remain largely undefined. Methods: Real-time PCR assays were used to detect the expression of miR-212 in human osteosarcoma tissues. MiR-212 mimics were introduced into MG63 and U2OS cells. Bioinformatic prediction was used to identify the potential targets of miR-212. Protein expression analysis, luciferase assays and rescue assays were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 26 publications
5
34
0
1
Order By: Relevance
“…Several studies has demonstrated many miRNAs expression signature associated with tumorigenesis, tumor growth, and metastasis in osteosarcoma [14][15][16]. In the present study, we found that miR-133a was expressed at lower levels in human osteosarcoma cell lines but at a high level in normal human osteoblastic cells.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Several studies has demonstrated many miRNAs expression signature associated with tumorigenesis, tumor growth, and metastasis in osteosarcoma [14][15][16]. In the present study, we found that miR-133a was expressed at lower levels in human osteosarcoma cell lines but at a high level in normal human osteoblastic cells.…”
Section: Introductionsupporting
confidence: 60%
“…Thus, miRNAs may potentially serve as molecular targets in cancer therapy. Several studies has demonstrated many miRNAs expression signature associated with cell proliferation, migration, and invasion in osteosarcoma [14][15][16]. Of the various miRNAs, miR-133a has been shown to exert tumor suppressor functions in many types of human cancers, including non-small cell lung cancer [21], gastric cancer [22], colorectal cancer [23], esophageal squamous cell carcinoma [24], ovarian cancer [25], and osteosarcoma [26].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, miRNAs may be potential targets for cancer therapy. A large number of studies reported that many miRNAs are involved in OS cell prolifera tion, migration and invasion (22)(23)(24). To date, the high expression of miR-663b in OS has been revealed however to the best of our knowledge the exact role of miR-663b in OS has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In general, miRNAs are composed of 19-25 nucleotides. Science magazine considered the discovery of miRNA to be one of the top ten scientific advancements in 2002and 2003(Garajova et al, 2014Luo et al, 2014). The relationship between miRNAs and tumors was first identified in chronic lymphocytic leukemia (CLL).…”
Section: Discussionmentioning
confidence: 99%